Ответ:
8(у-3)-а(3-у) = 8у-24-3а+ау
6(а-2)+5а(2-а) = 6а-12+10а+5а²=16а-12+5а²
3ах-ау+3бх-бу = 3х(а+б)-у(а-б)
аб-ас-7б+7с = а(б-с)-7(б+с)
типа так. наверное
смотря какой класс
(y-3)*(8+a)
(a-2)*(6-5a)
3x(a+b)-y(a+b)=(a+b)*(3x-y)
a(b-c)-7(b-c)=(b-c)*(a-7)
Здесь я сразу ответ написала
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
8(у-3)-а(3-у) = 8у-24-3а+ау
6(а-2)+5а(2-а) = 6а-12+10а+5а²=16а-12+5а²
3ах-ау+3бх-бу = 3х(а+б)-у(а-б)
аб-ас-7б+7с = а(б-с)-7(б+с)
типа так. наверное
смотря какой класс
(y-3)*(8+a)
(a-2)*(6-5a)
3x(a+b)-y(a+b)=(a+b)*(3x-y)
a(b-c)-7(b-c)=(b-c)*(a-7)
Здесь я сразу ответ написала